2023
DOI: 10.1073/pnas.2213765120
|View full text |Cite
|
Sign up to set email alerts
|

Disordered region encodes α-crystallin chaperone activity toward lens client γD-crystallin

Abstract: Small heat-shock proteins (sHSPs) are a widely expressed family of ATP-independent molecular chaperones that are among the first responders to cellular stress. Mechanisms by which sHSPs delay aggregation of client proteins remain undefined. sHSPs have high intrinsic disorder content of up to ~60% and assemble into large, polydisperse homo- and hetero-oligomers, making them challenging structural and biochemical targets. Two sHSPs, HSPB4 and HSPB5, are present at millimolar concentrations in eye lens, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 42 publications
(71 reference statements)
1
37
0
Order By: Relevance
“…2f and Extended Data Fig. 6 ) 36,51,52 . We fitted this NTD region into the cryo-EM density, corresponding to αB-crystallin residues LFDQFFGE (residues 23-30) ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…2f and Extended Data Fig. 6 ) 36,51,52 . We fitted this NTD region into the cryo-EM density, corresponding to αB-crystallin residues LFDQFFGE (residues 23-30) ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…2 A, black rectangle) and its “critical-sequence” ( Fig. 2 A, purple box) identified in CRYAB 39 . This region affects the structure and dynamics of the NTD with consequences for CRYAB chaperone activity ( 39 ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 68 . For CRYAB ssNMR studies reported an α-helix spanning residues 23–32 in CRYAB immediately preceding its critical-sequence 38 , 39 . The α-helix in the NTD of CRYAB will not fit the ACD central groove, implying that this part of the NTD will likely have to alter its conformation in the dimer 39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Holdases include many disparate proteins, such as the small heat shock proteins, , the α-crystallins, Hsp33, and HdeA, , among others. Holdases are thought to act in a more mechanistically simple manner by acting as a first line of defense to prevent widespread protein aggregation, later transferring their clients to the foldases for protein refolding. Although not requiring ATP, holdases can still be mechanistically complicated, using conditional disorder or heterogeneous oligomerization as regulatory mechanisms. , Some holdases do allow protein folding while bound, such as Spy. , …”
Section: Protein Chaperonesmentioning
confidence: 99%